Features of heavy metal input with flood sediments on the reclaimed lands of the floodplain agricultural landscape - Andrey V. Ilyinsky; Konstantin N. Evsenkin; Artyom A. Pavlov (Мелиорация и гидротехника, 2025)
Purpose: to study the features of pollutant input into the agro-ecosystem of reclaimed lands of the floodplain agricultural landscape depending on the level of sediment load. Materials and methods. The studies were carried out on arable floodplain reclaimed lands located near the town Ryazan. Sediments were collected using sediment traps. Soil samples were taken using the envelope method. Laboratory analysis of the samples for the content of acid-soluble forms of copper, zinc, lead, cadmium, nickel, chromium, mercury and manganese in sediments and soil was determined by atomic emission and atomic absorption spectrometry, and the arsenic content was determined by the photometric method. Results and discussion. The level of sediment load on the territory of the site (11.9–15.8 t/ha) was determined, at which pollutants enter the agricultural landscape in the following range of values: copper 15.1–20.7 mg/kg; zinc 9.2–97.4; lead 15.5–21.5; cadmium 6.56–22.8; nickel 26.2–34.0; chromium 30.2–70.3; mercury 0.029–0.042; arsenic 5.71–9.11; manganese 571–668 mg/kg. The degree of sediment pollution with heavy metals and arsenic corresponds to the highly hazardous category (Zc – 74.04). Based on the obtained experimental data, an empirical series of the input of the studied chemical elements into the agrolandscape with sediments was determined (Mn > Zn > Cr > Ni > Pb > Cu > Cd > As > Hg), and dependencies of the pollutant content in flood sediments on the level of sediment load were constructed. Conclusions. The studies indicate a high technogenic impact of precipitated sediments on soil and the need to organize agroecological monitoring for the pollutant content in flood sediments and underlying soil for the purpose of possible forecasting and prospects for using complex agro-reclamation techniques aimed at reducing the negative consequences of soil pollution in floodplain lands and increasing the environmental sustainability of the Oka River floodplain agrolandscape.